Fill the 5-liter container, pour water from that into the 3 liter container until that is full, You will now have 2 liters left in the 5 liter container.
Empty the 3-liter container, and then transfer the 2 liters from the 5-liter container into it.
Now fill the 5-liter container again, then pour water carefully from the 5-liter container into the 3-liter container until it is full - exactly one more liter.
The 5-liter container now has 4 liters in it.
Answer: x=7
Step-by-step explanation:
2x=17-3
2x=14
X=7
Answer:
Hence The composition
of the given function is
.
Step-by-step explanation:
Given:
![f(x) = x^2+2x-6](https://tex.z-dn.net/?f=f%28x%29%20%3D%20x%5E2%2B2x-6)
![g(x)=x+5](https://tex.z-dn.net/?f=g%28x%29%3Dx%2B5)
We need to find
.
Solution:
Now we can say that;
= ![f(g(x))](https://tex.z-dn.net/?f=f%28g%28x%29%29)
![(fog)(x) = (x+5)^2+2(x+5)-6](https://tex.z-dn.net/?f=%28fog%29%28x%29%20%3D%20%28x%2B5%29%5E2%2B2%28x%2B5%29-6)
Now Applying distributive property we get;
![(fog)(x) = (x+5)^2+2\times x+2\times5-6\\\\(fog)(x) = (x+5)^2+2x+10-6\\\\(fog)(x) = (x+5)^2+2x+4](https://tex.z-dn.net/?f=%28fog%29%28x%29%20%3D%20%28x%2B5%29%5E2%2B2%5Ctimes%20x%2B2%5Ctimes5-6%5C%5C%5C%5C%28fog%29%28x%29%20%3D%20%28x%2B5%29%5E2%2B2x%2B10-6%5C%5C%5C%5C%28fog%29%28x%29%20%3D%20%28x%2B5%29%5E2%2B2x%2B4)
Now Solving the exponent function we get;
![(fog)(x) = x^2+2\times x\times 5+5^2+2x+4\\\\(fog)(x) = x^2+10x+25+2x+4\\\\(fog)(x) = x^2+12x+29](https://tex.z-dn.net/?f=%28fog%29%28x%29%20%3D%20x%5E2%2B2%5Ctimes%20x%5Ctimes%205%2B5%5E2%2B2x%2B4%5C%5C%5C%5C%28fog%29%28x%29%20%3D%20x%5E2%2B10x%2B25%2B2x%2B4%5C%5C%5C%5C%28fog%29%28x%29%20%3D%20x%5E2%2B12x%2B29)
Hence The composition
of the given function is
.
Answer: 6.89
Step-by-step explanation:
9x+53>= 115
Subtract 53 from both sides
9x+(53-53) >115-53
9x>62
Divide both sides by 9.
9x÷9>62÷9 = 6.889